The future of rainwater recycling: assessing health risks and environmental impact - Pu, Jaan; Chukwuemeka, John; Mohamed, Radin Maya Saphira Binti Radin; Hamdan, Rafidah Binti; Hanmaiahgari, Prashanth Reddy; Moruzzi, Rodrigo [UNESP] (FapUNIFESP (SciELO), 2025)
This article examines the future of rainwater recycling through a study of numerous scholarly articles, research papers, and studies on rainwater collection, its advantages, potential health hazards, and environmental consequences. Rainwater collecting systems have gained popularity as feasible alternatives to traditional water resources because of their ability to alleviate water scarcity. A comprehensive search of peer-reviewed journal articles from 2004 to 2024 was conducted using Medline, PubMed, EBSCOhost, and Google Scholar, with specific search terms and Boolean operators. The assessment explores the importance of effective disinfection and filtration technologies for reducing microbiological pollutants. It also addresses the effects of toxic contaminants, such as heavy metals, highlighting the necessity of efficient management techniques. The review provides insights into optimising rainwater collection practices for better sustainability and resilience against the impacts of climate change by evaluating regional variances and global regulatory frameworks. This paper advocates for integrated approaches that are aligned with global water security goals and sustainable development objectives by providing information to policymakers, academics, and practitioners regarding the state and future directions of rainwater recycling.
O futuro do aproveitamento de agua pluvial: avaliando os riscos à saúde e o impacto ambiental
Keywords: clean water and sanitation (SDG 6); contaminants; environmental impacts; health risks; rainwater recycling